Personal and Family Drama of Simka Katić in the Novel Koreni by Dobrica Ćosić - Lazić, Nebojša; Lazić, Nebojša (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Through the fate of a novel’s heroine Simka Katić, Serbian writer Dobrica Ćosić (1921–2014) showed the individual and collective fate of women in the Serbian society during the 19th century. The tragedy of this woman comes from her desire to give birth to the male heir for herself and for the family she was getting married into. In despair, she cheats her husband with a servant and by this gesture, which defies the strict rules of patriarchal morality, she gives birth to the son named Adam, who becomes the inheritor of the Katić family, but she destroys her own life.